Troublemakers on the prowl: Analyst warns of forces out to destabilise tomorrow's polls - Malay, Mail (Malay Mail, 2013)
THE commotion in the run-up to the 13th general election tomorrow is believed to be orchestrated by parties to show Malaysia is no longer safe under the ruling government.